2013
DOI: 10.1038/gene.2013.60
|View full text |Cite
|
Sign up to set email alerts
|

Screen of whole blood responses to flagellin identifies TLR5 variation associated with outcome in melioidosis

Abstract: Melioidosis is a severe infection caused by the flagellated bacterium Burkholderia pseudomallei. The nonsense polymorphism TLR51174C>T is associated with improved outcome in Thais with melioidosis. We hypothesized that other TLR5 variants may modulate the host response and determine outcome in melioidosis. We genotyped 12 TLR5 variants selected de novo from the HapMap database and examined the association of each with cytokines induced by flagellin stimulation of whole blood from healthy Thai subjects. We foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Evidence suggests that ruminant TLR5 has undergone adaptive evolution which is still ongoing as SNPs were co-localised with predicted adaptive codons [ 22 ]. This would suggest that the interactions between flagellins and bovine TLR5 are drivers of evolutionary changes which may have functional consequences in terms of both infectious disease susceptibility and/or inflammatory disorders as described for humans [ 43 , 45 ]. On-going work is investigating the critical residues required for bTLR5 responses and the pathways induced by flagellin recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that ruminant TLR5 has undergone adaptive evolution which is still ongoing as SNPs were co-localised with predicted adaptive codons [ 22 ]. This would suggest that the interactions between flagellins and bovine TLR5 are drivers of evolutionary changes which may have functional consequences in terms of both infectious disease susceptibility and/or inflammatory disorders as described for humans [ 43 , 45 ]. On-going work is investigating the critical residues required for bTLR5 responses and the pathways induced by flagellin recognition.…”
Section: Discussionmentioning
confidence: 99%
“…76 Although functional genetic variations in TLR1 have been associated with death from sepsis in white Americans, TLR4 and TLR5 genetic variations but not TLR1 genetic variations have been linked to outcomes for melioidosis in the Thai population. 75,[78][79][80][81] Nevertheless, the rarity of fatal melioidosis in patients without risk factors in the Darwin prospective melioidosis study suggests that these and other yet to be determined variable genetic polymorphisms in human innate immune responses are likely to be considerably less important overall in determining outcomes from melioidosis than the presence of one or more of the recognized risk factors for melioidosis. 16 Although a vigorous cell-mediated immune response may protect against disease progression, 82,83 infection with human immunodeficiency virus does not appear to be a risk factor for developing melioidosis or for more severe disease or a fatal outcome.…”
Section: Global Distribution Of Melioidosis: Recent Expansion or Justmentioning
confidence: 99%
“…Narisara Chantratita et al. reported that TLR5 rs5744174 1846T>C was associated with broadly lower cytokine responses to flagellin in human blood . After measles vaccine stimulation, Neelam Dhiman et al.…”
Section: Discussionmentioning
confidence: 99%